Standard for clinical/nursing unit management in South Africa - Marie Muller (AOSIS, 2000)
The nursing unit manager is responsible and accountable for quality management of a clinical unit to facilitate quality nursing/midwifery care and education. The unit manager requires practice guidelines on nursing unit management, reflecting excellence and presented in the form of standards and criteria in the form of a user-friendly instrument. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.